Analysis of the Background of the Problems of Article 50B Paragraph 2 (C) of the Revision of the Broadcasting Law 2024 in the Perspective of Democratic Resilience - Hendra Pakpahan; Palupi Lindiasari Samputra; Margaretha Hanita (Ikatan Sarjana Komunikasi Indonesia, 2025)
The revision of the Broadcasting Law 2024, particularly Article 50B paragraph 2Â (c) which prohibits the